Prospective study to compare abdominal hysterectomy versus non- descent vaginal hysterectomy at a tertiary care hospital - Sheth, Paresh N.; Choudhary, Prema Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hysterectomy can be performed by vaginal, abdominal and via laparoscopic route. In the current scenario of importance of non-invasive surgery there has been increase in interest and requirement of vaginal hysterectomy for non-prolapsed uterus i.e. Non-descent vaginal hysterectomy (NDVH) due to scarless surgery. Gynecologist across the world continue to use the abdominal approach for a large majority of hysterectomies that may be performed vaginally despite well documented evidence which says that vaginal hysterectomy do have better outcome. This study aimed to find out to compare outcomes of NDVH and Abdominal hysterectomy (AH). Methods: The study is conducted at department of Obstetrics and Gynecology, at a tertiary care hospital Gujarat, India, between the periods of May 2018 to December 2019 of 100 patients. 50 Patients who underwent hysterectomy by abdominal route are taken as study group A and 50 Patients who underwent hysterectomy by vaginal routes are taken as group B. Results: Out of 100 women we have studied, duration of surgery, intra operative blood loss, intra operative complications, postoperative morbidity and duration of hospital stay, time required to resume normal work are less in group B (NDVH). Conclusions: It can be concluded that NDVH is feasible, safe and better alternative to abdominal hysterectomy for benign gynecological conditions. It also provides greater efficacy and safety with minimal invasiveness.